Answer:
AB - C² = 3x³ + x² + 6x - 9 ⇒ last answer
Explanation:
* Lets study the problem to solve it
- The variables are:
# A = x²
# B = 3x + 2
# C = x - 3
* At first lets find AB
∵ A = x² and B = 3x + 2
∴ AB = x²(3x + 2)
∵ x² × 3x = 3x³ ⇒ same base so we added the power
∵ x² × 2 = 2x² ⇒ coefficient of x² is 1 multiplied by 2
∴ AB = 3x³ + 2x²
* At second find C²
∵ C = x - 3
∴ C² = (x - 3)²
- To solve bracket to the power of 2 use this rule:
# square the first term + 1st term × 2nd term × 2 + square the 2nd term
∴ (x - 3)² = (x²) + (x) (-3) (2) + (-3)² = x² - 6x + 9
∴ C² = x² - 6x + 9
* Now lets find AB - C²
∵ AB - C² = 3x³ + 2x² - (x² - 6x + 9) ⇒ multiply the bracket by -ve sign
∵ -ve × -ve = +ve
∵ -ve × +ve = -ve
∴ AB - C² = 3x³ + 2x² - x² + 6x - 9 ⇒ Add the like terms
∴ AB - C² = 3x³ + x² + 6x - 9
* AB - C² = 3x³ + x² + 6x - 9